2014
DOI: 10.1242/jcs.134833
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 regulates mesenchymal stem cell differentiation into smooth muscle cells and development of contractile function in vivo

Abstract: Although soluble factors, such as transforming growth factor b1 (TGF-b1), induce mesenchymal stem cell (MSC) differentiation towards the smooth muscle cell (SMC) lineage, the role of adherens junctions in this process is not well understood. In this study, we found that cadherin-11 but not cadherin-2 was necessary for MSC differentiation into SMCs. Cadherin-11 regulated the expression of TGF-b1 and affected SMC differentiation through a pathway that was dependent on TGF-b receptor II (TGFbRII) but independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 92 publications
4
35
0
1
Order By: Relevance
“…Recently, our group reported that CDH11 but not CDH2 was necessary for MSC differentiation into SMCs [9] (Fig. 3).…”
Section: The Role Of Cdh2 and Cdh11 In Mesenchymal Stem Cell Diffementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group reported that CDH11 but not CDH2 was necessary for MSC differentiation into SMCs [9] (Fig. 3).…”
Section: The Role Of Cdh2 and Cdh11 In Mesenchymal Stem Cell Diffementioning
confidence: 99%
“…However, the mechanical and biochemical signals originating from cell-cell adhesion remain relatively unexplored in this context. Recent studies implicated adherens junctions in the maintenance of embryonic stem cell self-renewal potential, cellular reprogramming, hematopoietic stem cell engraftment and mesenchymal stem cell (MSC) differentiation into muscle [8, 9, 18]. Here we provide a brief review on the role of cadherins, in particular CDH2 and CDH11, in development and stem cell fate decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Fibroblasts play a critical role in wound closure through its contractile function as well as synthesis and remodeling of extracellular matrix (ECM), mainly collagen. Interestingly, loss of CDH11 diminished several key biological functions in smooth muscle, hair follicle, and fibroblast cells, including contractility, 21 migration capacity, 12 and ECM synthesis, 22 ultimately compromising the tissue mechanical properties. CDH11 was also reported to play a role in the response of fibroblasts to inflammatory mediators such as TNF-Îą.…”
Section: Introductionmentioning
confidence: 99%
“…12 Although there is limited information on atypical cadherins in vascular cells, cadherin-11 has been reported to be upregulated in SMCs in vein grafts 28 and required for in vitro differentiation of mesenchymal stem cells to SMCs. 29 The current findings are the first to establish a role for cadherin-11 in structural networking among SMCs. Recent adhesion force measurements by Hinz et al 30 have established that cadherin-11 bonds are stronger than those of N-cadherin.…”
Section: Arterioscler Thromb Vasc Biol May 2015mentioning
confidence: 54%